Pengaruh Pembelajaran Online, Penggunaan Bahan Ajar Interaktif Berbasis CTL, dan Intensitas Pemberian Tugas Terhadap Hasil Belajar PALIP SMKN 10 Surabaya - I'in Mutmainah; Susanti Susanti (Jurnal Pendidikan Akuntansi (JPAK), 2022)
Education in Indonesia is a benchmark for the development and the nation’s progress. However, the educational activities have been hampered since the Covid-19 pandemic, which requires the learning process to be distance learning or online. This can affect the student learning outcomes.The purpose of this study is to determine the effect of online learning, the use of CTL-based interactive teaching materials, and the intensity of assignment on the learning outcomes of government institutions/agencies accounting practicums. This type of research includes quantitative research which is analyzed using statistics and interpreted. Sampling using the Simple Random Sampling technique and calculated using the Slovin formula, that is 60 students in class XI AKL SMKN 10 Surabaya. The data collection instrument was a closed questionnaire which was then processed through the help of the SPSS V25 application through multiple linear regression tests. The results of this study are partially online learning has no effect on learning outcomes while the use of CTL-based interactive teaching materials and the intensity of assignment has a positive and significant effect on learning outcomes of government institutions/agencies accounting practicums. Meanwhile, simultaneously online learning, the use of CTL-based interactive teaching materials, and the intensity of assignment have a positive and significant impact on the learning outcomes of government institutions/agencies accounting practicums at SMKN 10 Surabaya. Simultaneously online learning, the use of CTL-based interactive teaching materials, and the intensity of assignment have contributed 60.5% to the learning outcomes of government institutions/agencies accounting practicums.